Proterozoic-early Paleozoic ophiolites of the Andean Basement of southern South America - Ramos, Victor Alberto (2000)
We describe a series of Middle Proterozoic to early Paleozoic ultramafic and mafic rocks in the basement of the Central Andes that have different geochemical attributes and paleogeographic settings. Several ophiolitic belts are identified on the basis of lithologic assemblages and geochemical characteristics, but only the most important belts are described here: the Western and Eastern Córdoba (Early Cambrian), Pie de Palo (Middle Proterozoic), Western Precordillera (Middle Ordovician), and eastern Cordillera Frontal (Proterozoic) belts. Most ophiolites in the Central Andean basement belong to one of two types: the harzburgite type and the lherzolite type. For example, in the metamorphic basement in the Western Córdoba belt of the Eastern Sierras Pampeanas, a harzburgite-type ophiolite is associated with important podiform chromite deposits whereas a lherzolite-type ophiolite of the Eastern Córdoba belt was emplaced in a backarc setting. The most ancient ophiolites at these latitudes are exemplified by the Middle Proterozoic Pie de Palo ophiolite, part of the Cuyania terrane, which is a Laurentian-derived block accreted to the protomargin of Gondwana during early Paleozoic time. The ophiolitic assemblage of the Western Precordillera includes serpentinized peridotites, ultramafic cumulates, layered gabbros, diabases, and basaltic pillow lavas. The ophiolites of the eastern Cordillera Frontal are emplaced within three distinctive belts in Precambrian metamorphic rocks. The dominant assemblage of the eastern Cordillera Frontal includes serpentinized peridotites, gabbros, basaltic dikes, and pillow lavas. As a whole, these ophiolite belts represent a complex system of sutures that record the accretionary history of the basement of the Central Andes in several tectonic episodes.